Synthesizing Switching Logic for Safety and Dwell-Time Requirement - Jha, Susmit; Gulwani, Sumit; Seshia, Sanjit A.; Tiwari, Ashish (ICCPS '10, April 13-15, 2010, Stockholm, Germany, 2010)
Cyber-physical systems (CPS) can be usefully modeled as hybrid automata combining the physical dynamics within each mode with discretized switching behavior between modes. Designers of CPS need to create models that satisfy safety and performance requirements. While the physical dynamics within each mode is usually defined by the parameters of the physical plant, the tricky design problem often involves getting the switching logic right. In this paper, we present a new approach to assist designers by synthesizing the switching logic, given a partial system model, using a combination of numerical simulation and fixpoint computation. Our technique begins with an over-approximation of the guards on transitions between modes. In successive iterations, the over-approximations are refined by eliminating points that will cause the system to reach unsafe states, and such refinement is guided by numerical simulation. In addition to safety requirements, we synthesize models to satisfy dwell-time constraints, which impose upper and/or lower bounds on the amount of time spent within a mode. We demonstrate using case studies that our technique quickly generates intuitive system models and that dwell-time constraints can help to tune the performance of a design.